Application Of The Problem Based Learning Model to Improve Student Learning Outcomes - Siti Musayadah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Problem-based learning is a problem-based learning model that integrates students' learning using problem-based learning. Based on the results of the researcher's observations, it was found that learning in class V at SDN 6 Ngabul was still centered on the teacher because the use of learning was still lecture-based. This study aims to determine learning outcomes when teachers use the PBL learning model. This research is Classroom Action Research (PTK). The results of the research show that the Problem Based Learning (PBL) learning steps that can be designed by teachers include problem orientation for students, organizing students to learn, guiding individual or group investigations, developing and presenting work results, analyzing and solving problem solving processes . The application of the PBL learning model can improve the mathematics learning outcomes of class V students at SDN 6 Ngabul for the 2020/2021 academic year with students' classical learning completion from 75% in the pre-cycle to 80% in the first cycle and 87% in the second cycle.